PENERAPAN ALGORITMA TURBO BOYER MOORE PADA APLIKASI MAKNA TUTUR BATAK BERBASIS ANDROID - Pratama, Minarni; Ginting, Guidio Leonarde; Hondro, Rivalri Kristianto (STMIK Budi Darma, 2018)
Follow said or speech act is to include a component of language and nonbahasa that describe the Acts language intact involving someone in the conversation for the delivery of the mandate. Batak is one of the tribes that are in the North sumatra province which has its own regional languages. Batak region has many languages spoken that have their own special meanings commonly used batak on each process festivities batak. In General, any person who has a marga batak in particular, will be required to perform its role in accordance with the roles have in attending ceremonies or else speak sapa with other families. Many said the word in the language area of the batak batak descent are sometimes obliged to remember it and sometimes there are that have yet to find out its meaning. It is an obvious problem for the people of batak especially for living in urban areas because of the technological developments that erode customs. The solution of these problems is by way of designing a media information in the form of the application is the meaning of the said in the batak are easily accessible and easily understood by the public. Word search techniques used in this research is the turbo algorithm boyer moore. The Turbo Boyer-Moore algorithm is an algorithm that was developed originally is Boyer-Moore Algorithm. The results achieved in this research is the application of a batak said meaning android can be installed on android smartphones and can be used offline.Keywords: Makna Tutur Batak, Algoritma Turbo Boyer Moore, Pemograman Android, Aplikasi Android